Analysis of Communication Patterns and Social Networks in Digital Propaganda Against Zionism in the Palestine-Israel Conflict - Nabila Fikriyah, Saniyah; Pramiyanti, Alila (Dinasti Research, 2025)
The analysis of communication patterns and social networks in digital propaganda aims to understand the mechanisms of the spread and reception of these messages in various parts of the world. Research on digital propaganda on social media has identified a number of important patterns in the spread of messages. This research provides significant insights into the role of social media in shaping the dynamics of international conflict, as well as how digital propaganda can influence public perceptions of complex issues. Using the Social Network Analysis (SNA) method, this research enriches the theoretical understanding of how interactions between actors on platforms such as Twitter or X affect the spread of information and the formation of public opinion. This research also expands knowledge about SNA metrics such as degree centrality, which can be used to identify key actors in the spread of digital propaganda.